Characterizing Bicycle Collisions by Neighborhood in a Large Midwestern City. Issue 2 (March 2014) - Chaney, Robert A.; Kim, Changjoo
Introduction . Local environmental factors provide important contributions to bicycle safety. The purpose of this study was to characterize bicycle collisions by neighborhood in Cincinnati, Ohio. Background . The majority of prior bicycle safety research has focused on helmet use, especially among youth. Studies that have considered the neighborhood have centered on the built environment and its facilitation of bicycling (e.g., connectivity of roads and road conditions). Other broad conditions may be associated with injury beyond the use of protective equipment and the physical environment. Method . This study sought to determine spatial clustering, local patterning, temporal differences (time of day and season of year), and significant neighborhood-level predictors of bicycle collisions. Bicycle collision data were obtained from the Cincinnati, Ohio Police Department. Conclusions . This study showed that collisions occur at higher rates in the south-central and southwest neighborhoods of Cincinnati, Ohio. There were seasonal and time-of-day differences with respect to collision rates with summer and afternoon being the most common collision times. Neighborhood ethnicity, population density and presence of public transportation were all significant predictors of bicycle collisions. These findings will be disseminated to local city authorities and bicycle advocacy groups.